Pengembangan Pendidikan Islam: Suatu Telaah Epistemologis - Syarif Hidayatullah (Al-Jami'ah: Journal of Islamic Studies, 1998)
Nowdays the world Indonesia facing the current of modernity and its challenges which flow very rapidly and clear away the strength of human life. Islamic education, as a part of historical reality of all human beings, does not escape these problems. The challenges brought out by the modernity to the Islamic education force all elements involved to decice their approaches. According, many efforts have been done including “revising the curriculum”, revitalizing the institution” and “the Islamization of knowledge” this paper does not aim to place itself as a complete and perfect “master plan” which is offered to overcome the challenge of modernity, rather, it is merely a descriptive-philosophical reflection of the historical reality which is faced by the Islamic education. It tries to stimulate “our mind” to seek some answer fot the challenges faced by the Islamic education by mean of demonstraction and/or reconstraction of the epistemological paradigm. This effort is meant to reach the “true” and basic aim in yhe Islamic Education System.in accordance with the program of islamization of knowledge. This epistemological reconstraction Indonesia desperately needed. These tow efforts are aimed to eliminate some “facts and impressions of the dichotomy perceived in the Islamic education by uniting religious sciences and secular sciences into one single discourse. This paper gives particular attention to the transformation of the IAIN (state Institute of Islamic Studies) and the 1997 curriculum, which are perceived as the “first promosing step” to support of the Islamization of knowledge as well as the epistemological reconstraction in the Islamic education, particulary in Indonesia.